Migrating to swift from web development - Liao, Sean (Apress, 2015)
Migrating to Swift From Web Development gives you the ability to create native iOS apps using the latest Swift programming language. Starting with preparing your latest Xcode 6 Integrated Development Environment and introducing just enough iOS application framework fundamentals, you'll understand how to create a simple but meaningful Hello Swift application for iOS 8 immediately. After the short IDE setup guide, this book will show you how to structure your iOS project from an existing mobile web app. Every topic comes with a tutorial project that you will create by yourself. You'll plan and structure your iOS apps using Xcode Storyboard, implementing use cases with detailed screens, and learn about managing data and working with remote services. Finally, you?ll experience a recap of the whole porting process by translating a mobile web app to iOS 8 from start to end. When you finish reading Migrating to Swift from Web Development, you'll be an iOS developer as well as a front-end web developer.